Competition-level differences on the lower quarter Y-balance test in baseball players - Butler, R. J.; Bullock, G.; Arnold, T.; Plisky, P.; Queen, R. (Journal of Athletic Training, 2016)
Context: Decreased performance in dynamic balance has previously been associated with a history of ulnar collateral ligament injury in baseball players. Previous research on dynamic balance in soccer players has shown that test performance depends on competition level. However, dynamic balance has yet to be examined in baseball players.